Photo Studio Booking Information System (Case Study: Reflection Photography Yogyakarta) - Sri Haryati; Chanifah Indah Ratnasari (Faculty of Industrial Technology Universitas Islam Indonesia, 2021)
There is no system used for booking a photo studio, making it quite difficult for customers to book a photo studio at Reflection Photography Yogyakarta. To book the photo studio, clients have to come in person, through WhatsApp chat, or by phone call. However, the studio is often slow in replying to WhatsApp chats from customers. Additionally, the recording of ordering data is still done manually using paper and transaction reports made using Microsoft Excel. The purpose of this research is to develop an information system to overcome these problems. The system built is web-based and uses the prototyping method. This system was tested by two tests, black-box and usability testing. For black-box test results, all the features tested show conformity as expected. As for the usability test results, all tested technical aspects showed 94.29% that the system considered as easy to use by users.